A critical review of the role of technology and context in digital health research. (June 2022) - Nielsen, Petter; Sahay, Sundeep
Digital health represents a research field dedicated to realising digital technologies' potential and developing knowledge about their feasibility and impacts. Yet, drawing on a critical review of the articles in the most prominent multidisciplinary digital health journals, this paper argues that the digital health field has not profoundly engaged with its core subject, namely technology. The features of digital technologies remain in the background, and research is disconnected from the complexities of healthcare settings, including multiple technologies, established practices and people. Instead, the overarching focus in the digital health literature is the processing capabilities of digital technologies and their posited impacts. This paper proposes a research direction in digital health where technology and the context of use take a more prominent role. It argues that realising the potential of digital health requires intensive investigation drawing on different disciplines, grounded on understanding healthcare processes, related informational needs and the concrete features of digital technologies.